Evaluation of Mastery of Physics Concepts with the RACH Model: Analysis Approach Using J Metrics - Samsun, Samsun .; Rahayu, Wardani; Arthur, Riyan Arthur (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to analyze mastery of understanding physics concepts in material motion kinematics material. Mastery of concepts is one of the important goals in the physics learning process. This research uses a case study approach with a post-test only one group design. The research sample consisted of 739 level 1 students. Instruments study consists of 28 multiple choice questions. The results of the research show that the majority of students have mastered the understanding of physics concepts the average ability is around -0.3032 to -0.0137 logit or lower than 0.0 logit. Scale theta covers a range from approximately -5.21 (for a score of 0) to 5.52 (for a score of 35). This means that students' abilities are distributed from very low to very high. Rasch models can be analyze mastery of understanding physics concepts well. Learning physics requires a learning process that can increase mastery of concepts.